Cases Abusing Brain Death Definition in Organ Procurement in China. (July 2022) - Paul, Norbert W.; Allison, Kirk C.; Li, Huige
Abstract: Organ donation after brain death has been practiced in China since 2003 in the absence of brain death legislation. Similar to international standards, China's brain death diagnostic criteria include coma, absence of brainstem reflexes, and the lack of spontaneous respiration. The Chinese criteria require that the lack of spontaneous respiration must be verified with an apnea test by disconnecting the ventilator for 8 min to provoke spontaneous respiration. However, we have found publications in Chinese medical journals, in which the donors were declared to be brain dead, yet without an apnea test. The organ procurement procedures started with initiating "intratracheal intubation for mechanical ventilation after brain death, " indicating that a brain death diagnosis was not performed. The purpose of the intubation was not to resuscitate the patient but rather was directly related to facilitating the explantation of organs. Moreover, it was unmistakably stated in two of these publications that the cardiac arrest was induced in these patients without brain death determination by cold St. Thomas cardioplegic solution or other cold myocardial protection solutions. This means that the condition of these donors neither met the criteria of brain death nor that of cardiac death. In other words, the "donor organs" may well have been procured in these cases from living human beings. Thus, brain death definition is abused in China by some individuals for organ harvesting, and a systematic investigation is needed to clarify the situation of organ donation after brain death in China.